Analysis of Determinants of Employee Engagement in the Creative Industries Sector Located in North Sumatra - Indajang, Kevin; Efendi, Efendi; Andronicus, Melkyory; Putra, Loist Abdi; Sudirman, Acai (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
The primary goal of this study is to examine how employee engagement in North Sumatra's creative industries sector is impacted by ethical leadership, self-efficacy, work-life balance, and perceived organizational support. The Purposive Sampling Technique was applied in this study. The sample's features include having more than a year of experience in a comparable role and not being an outsourced worker or a third party employed by the creative industry, which employs 210 people in total. The study's findings support the notion that work-life balance, self-efficacy, ethical leadership, and perceived organizational support all significantly and favorably impact employee engagement. The study's findings support the notion that work-life balance, self-efficacy, ethical leadership, and perceived organizational support all significantly and favorably impact employee engagement. According to this study, a comprehensive strategy that incorporates elements of moral leadership, self-assurance, work-life balance, and organizational support can successfully raise employee engagement in North Sumatra's creative industry sector.